Shaping the Future: Interdisciplinary Insights into Human Progress and Tomorrow's World - Adeoye, Moses Adeleke (FALASIFA : Jurnal Studi Keislaman, 2025)
This paper provides interdisciplinary insights into human progress and the potential trajectory of tomorrow's world. It explores scientific, philosophical and theological perspectives to offer a comprehensive understanding of how individuals, societies and the global community can navigate the complexities of the future and strive towards a more prosperous and sustainable world. The study explores the multifaceted nature of human progress, considering technological advancements, societal developments, ethical considerations and environmental impacts. Drawing on insights from fields such as sociology, psychology, economics and environmental science, the study presents a holistic view of the factors contributing to shaping the future of humanity. The philosophical underpinnings of human progress were examined, examining questions of ethics, morality and purpose in an ever-changing world. Exploring the philosophical traditions around the globe sheds light on the fundamental values that should guide our collective efforts towards a better future. The study also considers the role of theology in shaping the future, exploring the teachings of various religious traditions to uncover spiritual dimensions of progress and moral imperatives.